High-heat-flux performance limit of tungsten monoblock targets: Impact on the armor materials and implications for power exhaust capacity. (October 2022) - You, Jeong-Ha; Greuner, Henri; Böswirth, Bernd; Hunger, Katja; Roccella, Selanna; Roche, Helen
Highlights: Results of extensive high-heat-flux tests of tungsten monoblock-type divertor target mock-ups are presented. Impacts of various slow/short transient overloads on the armor materials and the joining interfaces are addressed. Comprehensive high-quality data comprising IR thermography, ultrasonic tests and electron microscopy are presented. Implications of the novel test results for the power exhaust requirements are discussed. Abstract: Development of a reliable high-heat-flux (HHF) technology is one of the crucial requirements of power exhaust strategy for a fusion reactor. The baseline HHF technology of the EU-DEMO, which inherited mostly the ITER technology, is based on the tungsten monoblock design and hot radial pressing joining technique. Thermal resilience and structural integrity under all off-normal transient events foreseen are essential prerequisites for validation of the technology towards the demonstration of full-scale prototype manufacture. Hence, the HHF performance of the baseline technology needs to be evaluated also in the transient overload regime. To this end, we conducted an extensive HHF testing campaign using small-scale test mock-ups of the tungsten monoblock target for two slow (10 s) overloads at 20 MW/m 2 (up to 2000 pulses) and 25 MW/m 2 (1000 pulses), and for a short (0.4 s) overload at 40 MW/m 2 (5000 pulses). Furthermore, excessive heat loads (32–37 MW/m 2 ) were applied beyond the armor melting event to test the structural stability at limit loads. IR thermography, ultrasonic inspection and electron microscopy (EBSD) delivered direct information and insight on the structural integrity and the impact on the armor microstructure. It was found that the tungsten monoblock target remained fully intact at least up to 1000 heating cycles at 20 MW/m 2 (10 s) and survived 2000 cycles without any major failure. At 25 MW/m 2 (10 s), the mock-ups remained nearly intact at least up to 500 heating cycles and survived 1000 cycles without critical failure. However, the armor surface showed substantial deformation roughening with the height of 1000 µm after 1000 cycles. At 40 MW/m 2 with short pulses (0.4 s), the mock-ups remained fully intact without any serious damage at least up to 5000 cycles. The mock-ups even withstood the limit heat load of 32 MW/m 2 at least for a few pulses. Under excessive overloads (33–37 MW/m 2 ) above the critical incident heat flux, armor melting preceded any other potential failures (e.g. pipe rupture by coolant boiling).